Landsat ETM-7 for Lineament Mapping Using Automatic Extraction Technique in the SW Part of Taiz Area, Yemen (Global Journal of Human-Social Science, 2013)
The application of remote sensing technology may cover many fields of studies especially in structure geology and mineral exploration where the remote sensing is a useful for lineaments and structure features extractions Landsat ETM-7 satellite data were used and band -5 was found as the most suitable band in automatic delineation The automatic lineament extraction process was carried out with LINE module of PCI Geomatica V9 1 based on automatic detection algorithms canny algorithms The comparison of the autom-atic lineament extraction and the published fault maps of the area in terms of total length number of lineaments and directions The number and the total length of the lineaments using automatic method were found to be more than the number and the total length of the faults in the fault map The directional analysis of the automatic lineament map was done with the reference of fault map of the area and the structure features measured in the field